Impact of administrative environment on opportunity and necessity entrepreneurship in Europe. - Justyna Anders (European Regional Science Association (ERSA), 2011)
The scope of the paper is to examine relationship between quality of administrative environment for business and propensity to become entrepreneur. Two different approaches to business activity are taken into account: opportunity and necessity entrepreneurship (Global Entrepreneurship Monitor, 2004). The analysis refers to period 2004-2009 and takes into account data for member states of the EU against the background of other selected economies: BRIC, Japan and the USA. The study is carried out to determine whether effects of regulation on GDP differences between developed and underdeveloped nations (Djankov et.al., 2006) can also be attributed to direct measures of entrepreneurship and can be also grasped also in a relatively homogenous sample of the EU members. Data sources comprise selected results of Doing Business study (start up procedures, regulation of ongoing activities, labour market regulation, registering property, closing a business) by World Bank and Study on Entrepreneurship in Europe by Gallup for the European Commission. Single-linkage clustering will serve as a basis for identification of homogenous groups of courtiers. The results will be then analysed in view of potential factors that differentiate the clusters i.e. legal origins, administrative culture, social capital, human capital and access to finance. The studies on regulation and start ups, research on barriers for entrepreneurship in Europe, studies of social institutions and their impact on economic development will be taken into account as a theoretical background.
Keywords: 330